Implementation of Murottal Al-Qur'an Therapy on Maternal Post Sectio Caesarea In Reducing Pain and Improves Sleep Quality - Nailah Azzahra, Balqis; Kartilah, Tetet; Nurhayati, Tetik; Asep Riyana (Asy-Syifa : Journal of Science and Technology Nursing, 2025)
Purpose: The purpose of this case study is to describe the implementation of Qur’anic murottal therapy in post-sectio caesarean mothers, its effects on pain reduction and sleep quality improvement, and its role as a non-pharmacological nursing intervention. Methods: This study employed a qualitative design using a case study approach involving two post-sectio caesarean mothers. The intervention consisted of listening to Qur’anic murottal therapy (Surah Ar-Rahman) for 15 minutes once daily over three consecutive days. Pain intensity was measured using the Verbal Rating Scale (VRS), while sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). Results: The results showed that both respondents experienced acute pain related to post-sectio caesarean surgical wounds. After the implementation of Qur’anic murottal therapy, pain intensity decreased from the severe pain category to the mild pain category. In addition, sleep quality improved from the poor category to the good category in both mothers. Conclusions: Qur’anic murottal therapy is proven to be effective in reducing pain intensity and improving sleep quality in post-sectio caesarean mothers. Therefore, this therapy can be recommended as an alternative non-pharmacological nursing intervention to help control pain and enhance sleep quality.